Graphene Architecture-Supported Porous Cobalt–Iron Fluoride Nanosheets for Promoting the Oxygen Evolution Reaction - Yanhui Lu; Xu Han; Yiting Zhang; Xu Yu (Nanomaterials, 2023)
The design of efficient oxygen evolution reaction (OER) electrocatalysts is of great significance for improving the energy efficiency of water electrolysis for hydrogen production. In this work, low-temperature fluorination and the introduction of a conductive substrate strategy greatly improve the OER performance in alkaline solutions. Cobalt–iron fluoride nanosheets supported on reduced graphene architectures are constructed by a one-step solvothermal method and further low-temperature fluorination treatment. The conductive graphene architectures can increase the conductivity of catalysts, and the transition metal ions act as electron acceptors to reduce the Fermi level of graphene, resulting in a low OER overpotential. The surface of the catalyst becomes porous and rough after fluorination, which can expose more active sites and improve the OER performance. Finally, the catalyst exhibits excellent catalytic performance in 1 M KOH, and the overpotential is 245 mV with a Tafel slope of 90 mV dec−1, which is better than the commercially available IrO2 catalyst. The good stability of the catalyst is confirmed with a chronoamperometry (CA) test and the change in surface chemistry is elucidated by comparing the XPS before and after the CA test. This work provides a new strategy to construct transition metal fluoride-based materials for boosted OER catalysts.